Comparison of infusion pumps calibration methods. (14th November 2017) - Batista, Elsa; Godinho, Isabel; Céu Ferreira, Maria do; Furtado, Andreia; Lucas, Peter; Silva, Claudia
Abstract: Nowadays, several types of infusion pump are commonly used for drug delivery, such as syringe pumps and peristaltic pumps. These instruments present different measuring features and capacities according to their use and therapeutic application. In order to ensure the metrological traceability of these flow and volume measuring equipment, it is necessary to use suitable calibration methods and standards. Two different calibration methods can be used to determine the flow error of infusion pumps. One is the gravimetric method, considered as a primary method, commonly used by National Metrology Institutes. The other calibration method, a secondary method, relies on an infusion device analyser (IDA) and is typically used by hospital maintenance offices. The suitability of the IDA calibration method was assessed by testing several infusion instruments at different flow rates using the gravimetric method. In addition, a measurement comparison between Portuguese Accredited Laboratories and hospital maintenance offices was performed under the coordination of the Portuguese Institute for Quality, the National Metrology Institute. The obtained results were directly related to the used calibration method and are presented in this paper. This work has been developed in the framework of the EURAMET projects EMRP MeDD and EMPIR 15SIP03.